Achieving sustainable cultivation of grain legumes Volume 2 - Sivasankar, Shoba; Bergvinson, David; Gaur, Pooran M.; Kumar, Shiv; Beebe, Stephen E.; Tamò, Manuele (Burleigh Dodds Science Publishing Limited, 2018)
Grain legumes are characterised by their nutritional value, an ability to grow rapidly and improve soil health. This makes them a key rotation crop in promoting food security. However, yields are constrained by factors such as pests and diseases as well as vulnerability to poor soils, drought and other effects of climate change.